2004
DOI: 10.1182/blood-2003-04-1048
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6–dependent gene expression profiles in multiple myeloma INA-6 cells reveal a Bcl-2 family–independent survival pathway closely associated with Stat3 activation

Abstract: Interleukin 6 (IL-6) is a growth and survival factor for multiple myeloma cells. As we report here, the IL-6-dependent human myeloma cell line INA-6 responds with a remarkably rapid and complete apoptosis to cytokine withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
114
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 76 publications
10
114
0
2
Order By: Relevance
“…In a previous study, we identified the proto-oncogene BCL3 as an IL-6 target gene (Brocke-Heidrich et al, 2004). Here, we show that IL-6 induces BCL3 expression in myeloma cells but not in hepatocellular carcinoma cells.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…In a previous study, we identified the proto-oncogene BCL3 as an IL-6 target gene (Brocke-Heidrich et al, 2004). Here, we show that IL-6 induces BCL3 expression in myeloma cells but not in hepatocellular carcinoma cells.…”
Section: Discussionsupporting
confidence: 47%
“…When comparing the gene expression profiles of INA-6 cells grown in the presence or absence of IL-6, we observed the induction of BCL3 (Brocke-Heidrich et al, 2004), originally identified as a candidate protooncogene overexpressed in certain cases of B-cell chronic lymphocytic leukemia as a consequence of a t(14;19) chromosomal translocation Ohno et al, 1990). High BCL3 expression has also been reported in a subgroup of anaplastic large-cell lymphoma (Nishikori et al, 2003).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Although the pathogenesis of the disease still remains unclear, it is well established that interleukin-6 (IL-6) plays an essential role in the malignant progression of MM [2][3]. Numerous reports suggest that IL-6 promotes survival and proliferation of MM cells through the phosphorylation of a cell signaling protein, Stat3 [4][5]. The Stat proteins are a conserved family of transcription factors implicated in regulating processes such as inflammation, survival, proliferation, metastasis, angiogenesis, and chemoresistance of tumor cells [6].…”
Section: Introductionmentioning
confidence: 99%